Relato de Atividade: “Faço Parte Dessa História” - Leme, Fernanda; Smaira, Fabiana Infante; Martins, Bianca Garcia (Revista de Graduação USP, 2017)
The present work consists in the report of an activity carried out with students in their first semester of the Nutrition course of the Universidade de São Paulo in 2014. This activity had as the proposal the construction of a timeline by students in the classroom about the history of the profession of nutritionist in Brazil. The aim of this report is to critically analyze the use of active teaching methodologies in higher education in order to transform the student from passive to active member in the classroom dynamics. The activity obtained good results by the view of the students who reported better use and dedication to the content with the dynamics used.